SINTESIS DAN KARAKTERISASI PERAK NANOPARTIKELBAKTERIAL SELULOSA BIONANOFIBER NANOKOMPOSIT - Muhamad Nasir; Chandra Risdian; Lilis Syarifuddin (Jurnal Kimia Terapan Indonesia, 2012)
Silver nanoparticle-bacterial cellulose bionanofiber nanocomposite (nano Ag-BSB) has been synthesized by using trisodium nitrate as reducing agent. The arrangement offiber in nano Ag-BSB nanocomposite has random shape after 26 confirmed by scanning electron microscopy (SEM)analysis. Nano Ag-BSB nanocomposite has average 64.1 nm in nanofiber diameter. Fourier infra red spectroscopy and X-ray diffraction analysis showed crystal structure in Ag-BSB nanocomposite is cellulose type L Crystalinity of BSB and Ag-BSB are 94 % and 89 %, respectively.This result showed that presence of silver nanoparticles in BSB decreased crystalinity of BSB. Ag-BSB nanocomposite has good performance in inhibitingE-Coli growth.Keywords: Silver nanoparticle; nanocomposite, bacterial cellulose bionanofibet; silver nanoparticlebacterial cellulose bionanofiber nanocomposit